The dark side of CEO inside debt: Evidence from stock price crash risk - Gholami, Amir; Elnahas, Ahmed (Journal of Corporate Finance, 2025)
Despite being thought of as a governance mechanism, CEO inside debt seems to distort firms' information environment. Our results indicate that CEO inside debt alters managerial orientation and incentives in a way that increases stock price crash risk. Our results are robust after addressing endogeneity using the instrumental variable (IV) approach, a difference-in-differences test based on the implementation of Internal Revenue Code Section 409 A Final Regulations, and Oster's omitted variable diagnostic test, and selection bias using the propensity score matching (PSM) and Entropy balancing (EB) approaches. The results are stronger for firms that are poorly governed, operate in less competitive industries, have lower institutional ownership, have higher information asymmetry, and pay less dividends. Further, the results are robust to controlling for CSR, local religiosity, tax avoidance, financial opacity, CEO power, and CEO as well as local political ideology.